Gambaran Duplex Sonography Plaque Arteri Karotis pada Pasien Hypertensive Heart Disease (HHD) - Lestari, Arum Lintang; Pudyastuti, Erlina; Fredy, Felix Chikita; Putri, Dewi Novita (ARKAVI [Arsip Kardiovaskular Indonesia], 2025)
Background: Hypertensive Heart Disease (HHD) is a condition characterized by increased blood pressure that causes disturbances in the heart's hemodynamic balance. One of its impacts is atherosclerosis, which can develop into the accumulation of hard fatty plaques in blood vessels. Early detection of atherosclerotic plaques can be performed through duplex sonography, a non-invasive imaging technique that allows for the evaluation of the structure and blood flow in the carotid arteries. Method: Case study on two patients with HHD. Results: In patient 1, B-mode duplex sonography examination showed stable plaques in the right and left carotid arteries with intima-media thickness (IMT) >2 mm. Meanwhile, in patient 2, unstable plaques were found in both carotid arteries with similar IMT values (>2 mm). Conclusion: Both patients with HHD showed the presence of atherosclerotic plaques in the carotid arteries with IMT >2 mm, indicating an increased cardiovascular risk. Duplex sonography can be an effective tool for detecting and monitoring the progression of atherosclerosis in patients with chronic hypertension.